2019
DOI: 10.3390/mi10080507
|View full text |Cite
|
Sign up to set email alerts
|

Optical Tweezers: Phototoxicity and Thermal Stress in Cells and Biomolecules

Abstract: For several decades optical tweezers have proven to be an invaluable tool in the study and analysis of myriad biological responses and applications. However, as with every tool, they can have undesirable or damaging effects upon the very sample they are helping to study. In this review the main negative effects of optical tweezers upon biostructures and living systems will be presented. There are three main areas on which the review will focus: linear optical excitation within the tweezers, non-linear photonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 179 publications
(412 reference statements)
0
86
0
Order By: Relevance
“…When free oxygen was removed from the system, either through introduction of a scavenging species, or by growing and trapping cells in an anaerobic environment, the damage was found to decrease to levels comparable with the control group, which was not exposed to the laser. Other studies have been performed that also seem to corroborate the hypothesis that oxygenation of the sample is a main cause of damage induced during optical trapping [79,80]. However, there…”
Section: Optical Trapping: Concerns For Biological Researchmentioning
confidence: 66%
“…When free oxygen was removed from the system, either through introduction of a scavenging species, or by growing and trapping cells in an anaerobic environment, the damage was found to decrease to levels comparable with the control group, which was not exposed to the laser. Other studies have been performed that also seem to corroborate the hypothesis that oxygenation of the sample is a main cause of damage induced during optical trapping [79,80]. However, there…”
Section: Optical Trapping: Concerns For Biological Researchmentioning
confidence: 66%
“…Detailed theoretical models for calculating the temperature changes of the trapped absorbing particles in OTs have been established under the approximation that the trapped object is an infinite medium with homogeneous thermal characteristics and with the consideration of particle absorption [14,81,86]. Other potential nonthermal cell damages caused by linear optical excitation, nonlinear photonic effects and reactive oxygen species/singlet oxygen as a consequence of high-intensity near-infrared laser radiation need to be considered when trapping biological objects [16,87]. In optical trapping of human RBCs, except for the undesirable temperature rise, studies have revealed the OTs-induced deoxygenation of the trapping site on the RBC surface that is proportional to the trapping power [88] and have observed cell membrane ionization, inactivation and ejection from the trap by the thermally produced (radiometric) force induced by high power infrared laser trapping [89][90][91].…”
Section: Thermal and Nonthermal Damage To Biological Objects By Opticmentioning
confidence: 99%
“…As with any tool, there are certain drawbacks and shortcomings of OTs technique in biological research. The trapping wavelength and strength are restricted by the potential thermal and nonthermal damage caused by the trapping light [16]. The difficulties of in vivo applications of OTs arise from the limited penetration depth of the trapping laser in biological tissues [153].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other relevant source of damage in OT is the production of heat due to laser light absorption: the photothermal effect (Berns, 2007b;Blázquez-Castro, 2019). Heat production starts with photon absorption.…”
Section: Mechanisms Of Damage In Otmentioning
confidence: 99%